A Publisher, a Citation Index, and an Unequal Global Research Economy - Mills, David (International Higher Education, 2024)
The roots of today’s unequal global science communication system trace back to the aftermath of World War II. US government funding for basic research generated a flood of scientific papers, opening up opportunities for commercial publishers. New information management tools were created, including the first scientific citation index. Commercial publishing infrastructures became a foundation for the globalization of higher education and research. A more equitable future depends on a different model of ownership and control.